Accelerated lifetime testing of thin-film solar cells at high irradiances and controlled temperatures - Burlafinger, Klaus; Strohm, Sebastian; Joisten, Christoph; Woiton, Michael; Classen, Andrej; Hepp, Johannes; Heumüller, Thomas; Brabec, Christoph; Vetter, Andreas (Progress in Photovoltaics, 2021)
Within this study, we investigate the intrinsic photostability of thin-film solar cells, here organic photovoltaic cells. Since degradation under natural sun light proceeds within the timeframe of months and years, the process needs to be speeded up for fast material analysis and screening, using high-concentration accelerated lifetime testing (high-C ALT). For this purpose, we established setups allowing irradiances of up to 730 sun equivalents (SE). One key finding of our study is that accelerating the testing procedure by such large intensities is possible but a precise measurement and control of the solar cell temperature is absolutely essential. Accordingly, we developed an innovative method of determining the temperature of the active layer which offers significant advantages over commonly used measurement methods. Furthermore, it was found that the degradation process under high illumination densities can be well described by a stretched exponential law. We demonstrate that the temperature kinetics of P3HT:PCBM was found to be Arrhenius governed with an activation energy of 27.2 kJ/mol under continuous illumination of 300 SE. Finally, it was shown that the velocity of light-induced degradation of short-circuit current depends linearly on the used irradiance dose at a given temperature starting from normal illumination conditions up to at least 300 SE. This makes high-C ALT a very valuable tool for swift screening of the lifetime of novel thin-film solar cells and materials.
CRIS-Team Scopus Importer:2021-11-26
Keywords: accelerated degradation; high irradiances; temperature check

A top-down strategy identifying molecular phase stabilizers to overcome microstructure instabilities in organic solar cells - Zhang, Chaohong; Heumüller, Thomas; Leon, Salvador; Gruber, Wolfgang; Burlafinger, Klaus; Tang, Xiaofeng; Perea, Jose Dario; Wabra, Isabell; Hirsch, Andreas; Unruh, Tobias; Li, Ning; Brabec, Christoph (Energy and Environmental Science, 2019)
The operational stability of organic solar cells (OSCs) is the essential barrier to commercialization. Compared to thermally-induced degradation, photo-stability of OSCs is far away from being resolved. Here, we demonstrate that the thermal- and photo-degradation of metastable bulk-heterojunction OSCs are governed by the same mechanism. Understanding the fundamental principles behind this mechanism is of significant importance to fully address the instability issues. Structural incompatibilities between the donor and acceptor molecules are identified as the main origin of the instability. Further, we introduce a top-down approach mainly based on their melting temperature and interaction parameters to rationally screen molecular phase stabilizers from a database with more than 10000 small molecules. Eventually, five chemicals were selected to validate our concept and tested in unstable organic solar cells. 1,4-Piperazine, which possesses a high melting point, good miscibility with polymers and the capability of forming inter-molecular hydrogen bonding, can indeed stabilize the mixed amorphous phases, leading to significantly improved stability of otherwise metastable OSCs.<br

Infrared Absorption Imaging of Water Ingress Into the Encapsulation of (Opto-)Electronic Devices - Hepp, Johannes; Vetter, Andreas; Langner, Stefan; Woiton, Michael; Jovicic, Gordana; Burlafinger, Klaus; Hauch, Jens; Camus, Christian; Egelhaaf, Hans-Joachim; Brabec, Christoph (IEEE Journal of Photovoltaics, 2019)
Water ingress into the encapsulation of electronic devices is a serious issue, especially for organic and perovskite-based electronics. In order to guide the development of suitable barrier materials and design, a reliable, fast, and non-destructive analysis tool is required. In this work, an imaging setup is presented, which is based on selective infrared (IR) radiation sources and a mid-IR sensitive camera that uses the absorption hand of water around 1920 nm and a reference band. This system enables us to monitor the distribution of water concentration inside the packaging of devices and its change over time. Our measurement is capable of detecting the local presence of water down to the mg/m(2) concentration range in a wide variety of encapsulation materials. The new tool allows identifying the pathways of moisture ingress into the encapsulation along with the corresponding diffusion coefficient. Thus, it provides fast and reliable analysis of humidity related failure mechanisms, and consequently helps to improve the design of encapsulation materials and processes.
Keywords: Degradation; diffusion processes; optical signal detection; organic photovoltaics (PVs); packaging

Maximizing concentrated solar power (CSP) plant overall efficiencies by using spectral selective absorbers at optimal operation temperatures - Burlafinger, Klaus; Vetter, Andreas; Brabec, Christoph (Solar Energy, 2015)
Selective absorbers for CSP plants to suppress thermal losses and to increase the efficiency is a promising topic and strong scientific efforts have been spent on how to design and realize such materials. However, there has been no comprehensive optimization analysis of the overall efficiency of CSP plants with selective absorbers.We performed a comprehensive computational parameter study of operation temperature and optical properties of the absorber and investigated their effect on the overall plant efficiency in dependence of sun light concentration up to C=2000 suns. Optimal operation temperatures were shown not to exceed 1383. K. By using selective absorbers instead of a black body or currently used materials, our assessment yields a potential electrical power output gain of up to around 35%. Our investigations also provide the optical parameters of an ideal (perfect selective) absorber. Its optimal cut off wavelength λcut lies around 2.4. μm for concentration factors below 120 and above 600 suns. For C in the range of 120-600 suns the value of the cut off wavelength is 1.79. μm. Simulating non-ideal (realistic) absorption properties, it was found that the strongest influence is caused by high absorption at low wavelengths. Low emittance at longer wavelengths plays a less important role. Also the sharpness of the transition from high absorption to low emittance plays a minor role regarding overall plant efficiency. As a rule of thumb, the cut-off wavelength should be at around 2.4. μm when assuming realistic (non-ideal) spectral selectivity. Finally, the theoretical maximum overall efficiency of a CSP plant achievable by an ideal selective absorber was calculated to up to 73% at 2000 suns and even up to 65% for a selective absorber with realistic optical properties.
Keywords: Absorber; CSP; Optimal operation temperature; Overall efficiency; Selective; Spectral

Ultrafast screening method for assessing the photostability of thin-film solar cells - Vetter, Andreas; Burlafinger, Klaus; Brabec, Christoph (Electrical Engineering, 2016)
Commercial success of optoelectronical devices such as solar cells depend strongly on lifetime next to production costs and power conversion efficiency. While a steep decrease in production costs and significant increase in efficiency have been achieved, lifetime still plays often a limiting factor, in particular, in case of highly innovative new device types. Lifetime tests measuring the stability of devices without external influences (i. p. water) generally take very long time due to the required long lifetime of optoelectronical devices. We established a novel accelerated lifetime test (ALT) setup which may increase the test speed by a factor of several hundred. We verified the setup and the applicability of our ALT measurement routine with an experiment on a well-studied innovative thin-film solar cell type (P3HT:PCBM).
Keywords: ALT; Optoelectronics; Organic photovoltaics; PV; Solar cell; Thin film